PENGARUH BUDAYA ORGANISASI, GAYA KEPEMIMPINAN DAN STRESS KERJA TERHADAP TURNOVER INTENTION KARYAWAN PADA PT. SEMEN BATURAJA (PERSERO) TBK - Deiby Ingrit Tiwa; Noviansyah (Jurnal Manajemen Bisnis Unbara, 2025)
The data analysis technique used is multiple linear regression. Based on the results of the analysis with the t-test, it shows that Organizational Culture (X1), Leadership Style (X2) and Work Stress (X3) have a significant effect on Employee Turnover Intention (Y) at PT Semen Baturaja (Persero) Tbk, obtained tcount Organizational Culture (X1 ) is 4.341 with a ttable of 2.00958 because tcount>.ttable is 4.341>2.00958 then H0 is rejected and Ha is accepted, meaning that there is a significant influence between Organizational Culture and Turnover Intention, tcount Leadership Style (X2) of 2.283 with a t table of 2.00958 because tcount> ttable is 2.283> 2.00958 then H0 is rejected and Ha is accepted, meaning that there is a significant influence between Leadership Style and Turnover Intention, tcount Job Stress (X3) of 2.295 with t table of 2.00958 because tcount> ttable namely 2.295> 2.00958 then H0 is rejected and Ha is accepted, meaning that there is a significant influence between Job Stress and Employee Turnover Intention at PT Semen Baturaja (Persero) Tbk